Comparison of the microstructure and properties of a series of Mg-Zn metallic devices on biomedical applications. Issue 2 (April 2019) - Zhang, Tao; Dai, Yilong; Yan, Yang; Zhang, Yu; Yu, Kun; Liu, Hui; Fang, Hongjie; Luo, Xier; Li, Li
Magnesium alloys have been investigated as biodegradable metallic materials because of their good biocompatibility with natural bone, while zinc has basic safety properties for biomedical applications and is one of the nutritionally essential elements for the human body. The microstructures and properties of some novel designs of bio-Mg-Zn alloys are studied to provide implantations which have an improvement in mechanical properties and corrosion resistance.